ANALYSIS OF ITS2 AND trnH-psbA IN PLANT SPECIES IN MALAYSIA - Ang, Hui Phing (2018)
DNA barcoding is important because it helps to do the identification of illegal trading as well as substitution of either accidental or purposeful replacement of herbs with cheaper alternatives in herbal medicine. Scientists or researchers can also determine the type and the number of plants present in a country and take action to protect the species from extinction. However, there is the possibility that barcoding success was affected by plants sourced in different countries as they may have their own evolutionary pathway based on the different selection pressures, hybridizing, and mutating. Success also depends on the loci used for barcoding. Hence, this study checks on the ability of the ITS2 and trnH-psbA in identification of three different plant groups, in the families Malvaceae (Hibuscus rosa-sinensis), Jasminaceae (Jasminum multiflorum) and Verbenaceae (Clerodendrum thomsoniae) found in Malaysia, when compared to a database populated with samples from elsewhere. Three samples of each species were collected, and the DNA isolated followed by polymerase chain reaction and sequencing. Finally the sequences were compared to the database using BLAST and a maximum likelihood analysis was carried out to create a phylogenetic tree with the best model. By using BLAST, Clerodendrum thomsoniae was correctly identified by both trnH-psbA and ITS2, while Hibiscus rosa-sinensis was correctly identifies using trnH-psbA but failed by ITS2 due to its complex ancestry. Jasminum multiflorum was unable to be identified by both trnH-psbA and ITS2 due to lack of these sequences for this species in the public database. However, all three species could be discriminated by tree topology